Pedagogias porvir com currículos e infâncias em dissidências - João Paulo de Lorena Silva (2024)
Childhoods in gender and sexuality dissidence move through different territories in contemporary times. This doctoral thesis, which is cartographic in nature, moves through different territories with the general aim of mapping the pedagogies and curricula invented in the encounter with these childhoods. It is a cartography that followed and recorded the family and school journeys of children who recognise themselves and/or are socially read as trans, pansexual, queer, and effeminate. Ten children, five mothers, eight teachers, two educational counsellors, a teaching assistant, an educational assistant, and a health professional took part in the research. The research carried out for this thesis sought to understand how children who experience dissident childhoods trigger signs of transition in their families and schools, and to analyse what these signs teach and what can be learned from them. This thesis shows that the novelty inaugurated and disseminated by these childhoods questions pedagogies and curricula, calling on them to transition and make transition, displacement, and immobile journeys the subject of a pedagogical and curricular process that is done in act. Working with concepts drawn from philosophies of difference, queer studies and post-critical curricular perspectives, such as: dissidence, hospitality, body, gender, sexuality, pedagogy, curriculum, agency, resistance and experimentation, this thesis shows the different movements made in pedagogy and curriculum when dissident children and their families express their desires to live and confront the adversities that come their way. The general argument of this thesis is that the assumed arrival of dissident childhoods on school territory, in alliance with an external curriculum, has demanded the creation of pedagogies that are hospitable, that hesitate, that operate through queer affections and that deal with the urgency involved in a life. Such pedagogies are conducive to the creation of other curricula, such as open-door curricula, that stutter, operate with sensations on the surface of the skin and confront gender and sexuality norms. This thesis shows that these different pedagogies and the curricula they demand are not given in advance, do not pretend to be universal and do not want to prescribe the best path, the truth to be assimilated or what needs to be done to save children from the normativity of gender and sexuality. Contrary to these transcendent and teleological assumptions, mapped pedagogies work in such a way as to host the foreignness of childhoods in dissent; to create curricula that are open to difference; to make curricula stutter and open up to the language of experimentation; to ally bodies and compose with sensations; to create skin-deep curricula; to make transgender children visible and to invent possible paths to house childhoods in their multiplicity. What is done in these pedagogies and in the curricula that are invented from them is an ethical and immanent exercise in experimentation, in composing with the sensations and affections that ask for passage. An exercise that involves opening the body to the creation of possibilities in pedagogical practice, in curricular practices and in the life that is sewn into the school territory.